Construction of alginate beads for efficient conversion of CO2 into vaterite CaCO3 particles. (September 2022) - Zhang, Hao; Zhang, Tuo; Zang, Jiachen; Lv, Chenyan; Zhao, Guanghua
Abstract: CO2 is a greenhouse gas and a major contributor to global warming. Efficient conversion of CO2 into high value-added food materials represents a promising strategy to decrease CO2 concentration. In this study, we reported that Ca 2+ -crosslinked alginate beads loaded with carbonic anhydrase (CA) can efficiently catalyze conversion of CO2 into porous vaterite CaCO3 particles via a carboxymethyl cellulose (CMC) inducing process. CA encapsulated within the Ca 2+ -crosslinked alginate beads maintained around 100% activity of its original activity after 10 assay cycles. Functionally, the CA-loaded alginate beads facilitated conversion of CO2 into porous vaterite CaCO3 particles with high CO2 removal efficiency in the presence of carboxymethyl cellulose. Notably, such vaterite CaCO3 particles can be explored for adsorption of astaxanthin with higher loading capacity (2.0 wt %), consequently improving the photo- and thermal-stability of this pigment. Graphical abstract: Image 1 Highlights: Carbonic anhydrase loaded within alginate beads serves as an edible CO2 absorber. These synthesized alginate beads convert CO2 into vaterite CaCO3 particles via CMC. The obtained porous vaterite CaCO3 particles have high astaxanthin loading capacity. The vaterite CaCO3 particles greatly improve the photothermal stability of astaxanthin.